Analisis Efektivitas Sistem Pemrosesan Sertifikat Tanah (Studi Kasus Pada Kantor Pertanahan Kota Metro) - Prasetyawati, Salsabila Mardhiyah; Suyanto, Suyanto; Zanaria, Yulita (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the procedure for processing land certificates at the Metro City Land Office. The type of research used is interactive quantitative research. The data analysis technique used is using triangulation with the source means comparing and checking back the degree of confidence of an information obtained through time and different tools in qualitative methods. The results showed that the Land Certification Services in Metro City Regency had been running well, these qualities included: Direct evidence, namely continuous socialization, with complete and modern equipment, and the results achieved for three years were 10,207 certified plot of land. Reliability, namely carrying out a fast and thorough service process in accordance with established procedures. Responsiveness, namely responding clearly and quickly to complaints from the community regarding land issues. Assurance is the ability and knowledge of good and transparent Larasita officers in terms of costs for certification. Empathy is a good attitude, courtesy and a little attention from officers to the community using Larasita services. The supporting factors include: regulations, organization, income, abilities and skills, and service facilities. Meanwhile, the inhibiting factor is the lack of public awareness to carry out land certification.